Pendugaan Area Kecil Persentase Anak-anak Usia Kurang dari 18 Tahun yang Hidup di Bawah Garis Kemiskinan Tingkat Kabupaten/Kota di Indonesia Tahun 2020 - Jayanti Wulansari; Novia Permatasari; Azka Ubaidillah (Politeknik Statistika STIS, 2022)
The rapid spread of the COVID-19 pandemic has caused a global crisis, including in Indonesia. One group at high risk of being affected during a crisis is children. Since their nature is dependent on others, decreasing income in the household makes children vulnerable to poverty. Child poverty is a condition where children cannot meet their basic needs. The percentage of children under 18 years living in poverty is one of the child poverty indicators. Unfortunately, this indicator is only available at the national and provincial levels. Data availability for small areas is required to support the acceleration of poverty alleviation, which is the goal of the SDGs and the 2020-2024 RPJMN. This study aims to obtain an estimate of the percentage of children under 18 living in poverty at the regencies/municipalities level using the SAE EBLUP. The result shows that the SAE EBLUP method is able to produce estimation with smaller and better MSE and RSE than the direct estimation.